2021
DOI: 10.1111/ijfs.15226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different thawing methods on microstructure and the biochemical properties of tilapia (Oreochromis niloticus) fillets during frozen storage

Abstract: This study investigated the effects of different thawing methods (water immersion thawing [WIT, 25 °C], air thawing [AT, 25 °C] and refrigerator thawing [RT, 25 °C]) on the biochemical properties and microstructure of tilapia (Oreochromis niloticus) fillets during storage at À18 °C for 6 months. The results indicated that the thawing time for WIT, AT and RT were approximately 7, 83 and 616 min, respectively. Thawing and cooking losses in the RT samples were significantly lower than those in WIT and AT samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Also in the same study maximum decrease in moisture content was in the microwave thawing (77.27% on the first day, 66% on the 60 th day). Wang et al (2022) studied the effects of different thawing methods (water immersion thawing, air thawing and refrigerator thawing) on the biochemical properties of tilapia (Oreochromis niloticus) fillets during storage at -18°C for 6 months. According to the thawing and cooking losses refrigerator thawing is suggested to be an effective thawing method similar with our study to minimise quality change during frozen storage.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the same study maximum decrease in moisture content was in the microwave thawing (77.27% on the first day, 66% on the 60 th day). Wang et al (2022) studied the effects of different thawing methods (water immersion thawing, air thawing and refrigerator thawing) on the biochemical properties of tilapia (Oreochromis niloticus) fillets during storage at -18°C for 6 months. According to the thawing and cooking losses refrigerator thawing is suggested to be an effective thawing method similar with our study to minimise quality change during frozen storage.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that chilled air thawing (CAT) is an effective thawing method to protect the structural integrity of muscle fibers, water-holding capacity and protein denaturation of fish fillets during frozen storage. 24 However, taste is one of the most important metrics in determining consumers' willingness to purchase. To the best of our knowledge, few studies have elucidated the relationship between frozen storage period and thawing method of frozen aquatic products with respect to taste substances.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we only evaluated the effects of frozen storage periods and thawing methods on protein denaturation and microstructure of tilapia fillets, obtaining interactions among the indicators. The results showed that chilled air thawing (CAT) is an effective thawing method to protect the structural integrity of muscle fibers, water‐holding capacity and protein denaturation of fish fillets during frozen storage 24 . However, taste is one of the most important metrics in determining consumers' willingness to purchase.…”
Section: Introductionmentioning
confidence: 99%
“…These new thawing methods have their own advantages and disadvantages and need to be optimized. However, most of the literature tend to focus on the influence of a single factor for a certain thawing method, or the comparative study of different thawing methods (Wang et al., 2021), and rarely involve the multiparameter optimization of the same thawing method. In addition, whether for the merchants or the consumers, the thawing time, the thawed meat quality, and the system energy consumption are all the indexes that need to be evaluated.…”
Section: Introductionmentioning
confidence: 99%